Type 1 diabetes: from the dream of automated insulin delivery to a fully artificial pancreas - Phillip, Moshe; Kowalski, Aaron; Battelino, Tadej (Nature medicine, 2024)
Automated insulin delivery systems have transformed the care of people living with type 1 diabetes and continue to move closer to the ultimate goal of a fully autonomous artificial pancreas. Automated insulin delivery systems have transformed the care of people living with type 1 diabetes and continue to move closer to the ultimate goal of a fully autonomous artificial pancreas.